STATE AND PROSPECTS OF GROUNDWATER USE IN THE AQUIFER OF THE FRACTURED ZONE OF CRYSTALLINE ROCKS - Lyuta, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
As a result of the aggression of the neighboring state, the problem of providing the population of Ukraine with drinking water from different sources became more acute. Groundwater in this sense compared to surface water has a number of advantages, especially protection from pollution and proximity to the consumer. It is necessary to diversify the sources of water supply to the population, to use all principle aquifers containing water of drinking quality. However, groundwater resources are distributed very unevenly over the territory of Ukraine – most of them are concentrated in the northern and western regions, while resources in the southern regions are limited. In addition, the main aquifers of the territory of Ukraine are characterized by a complex chemical composition, determined by natural and anthropogenic factors. A large part of Ukraine is occupied by the Ukrainian shield, the natural conditions of which do not contribute to the formation of significant groundwater resources. The aim of the study is to analyze the qualitative state of groundwater aquifer in the fractured zone of the Archean-Proterozoic crystalline rocks. For this purpose, information on the use and groundwater quality composition of the studied aquifer was collected and analyzed. As a result, patterns of spatial distribution of macro-components in groundwater aquifer in the fractured zone of crystalline rocks were found. These regularities are recommended to take into account in the process of groundwater monitoring and its economic and drinking use. Despite the extremely uneven distribution of groundwater in the fractured zone of crystalline rocks, in most areas there are prospects for a significant increase in groundwater production from this aquifer.